Empowering Sustainability through Arduino- Enhanced Experimentation with Natural Fiber Filters for Air Purity in Contextual Teaching Approach to Support Sustainable Development Goals (SDGs) - Harianti, H.; Riandi, R.; Kadarohman, Asep; Nandiyanto, Asep Bayu Dani; Fiandini, Meli; Prajayanti, Atiek Octaria (Journal of Engineering Education Transformations, 2025)
This research was conducted to develop science learning for vocational students related to problems that are currently one of the focuses in sustainable education, namely air quality which has adverse effects on humans. Science learning with a contextual approach will be more easily understood by students, accompanied by experiments that can be done directly by students. This research uses the experimental method by starting with the manufacture of experimental equipment related to air pollution. Indonesia is rich in natural fiber, Thus, it can be used as a filter to reduce air pollution produced by motor vehicles, the majority of which are owned by vocational school students. The tools made for this experiment are very affordable and can simultaneously measure air quality before and after the use of filters with natural fiber in motorcycle exhaust. The measuring instrument used to measure air quality uses an Arduino Uno device and an MQ-135 sensor. This experiment set is one of the innovations in education. The learning that has been carried out has shown a significant increase in student learning outcomes, although there are still misconceptions among students. The results also show that students are motivated to follow this learning and become aware of sustainable development, especially related to air pollution.